Asupan Inhibitor dan Enhancer Zat Gizi Besi yang Berhubungan dengan Status Anemia pada Remaja Putri di SMPN 16 Kota Jambi - permata, yuyun (Prosiding Seminar Kesehatan Nasional, 2024)
The high prevalence of iron nutritional anemia is caused by inadequate intake of iron for daily needs and disruption of body absorption so that iron deficiency for a long time will develop into anemia. This study aims at the relationship among iron consumption, inhibitors, and enhancers, and anemia status in teenage females. Study employed technique with a cross sectional sample of 60 teenage females chosen at random. Questionnaires, Food Recall, and 24-hour Food Frequency are some of the measurement devices employed. Since July 2022, a questionnaire has been distributed to SMP Negeri 16 in Jambi City. The participants in the study were 319 teenage females from SMP Negeri 16 in Jambi City. The sample of study is (FFQ). Univariate and bivariate data analysis were used (chi square test). According to the univariate analysis, the majority of the teenage females in SMP Negeri 16 Jambi City were categorised as anaemic (58.3%), frequently consumed inhibitors of iron, and seldom consumed enhancer iron nutrients. Chi-square analysis revealed a connection between anaemia status iron nutrient inhibitors (p-value = 0.016), and iron nutrient enhancers (p-value = 0.030). There is a substantial link between iron consumption, inhibitors, and enhancers among teenage girls at SMP Negeri 16 Jambi City. As a result, young women should restrict their intake of iron-inhibiting and iron-enhancing foods. Anemia, iron consumption, inhibitor and enhancer intake, teenage female.